La Götterlehre di Karl Philipp Moritz. Nell'officina del linguaggio mitopoietico degli antichi - CONGREGATI, SARA (Biblioteca di Studi di Filologia Moderna, 2020)
The unpublished translation of Götterlehre (1791) by K.Ph. Moritz presents the mythopoietic process of the Ancients by means of the tale of the origins of the numinous and of its ekfrastic structuring into the great mythical representations of the Greek-Roman world. In the background of Moritz's visit to Italy (1786-1788) and of his fruitful friendship with Goethe, the introductory essay illustrates the theoretical premises of the specific aesthetic itinerary covered by a work of classical mythology conceveid as Dichtung and codified by a very original and universal Sprache der Phantasie, emblematic figural language that refers to the iconic character of the text with the rich repertoire of lithographies based on drawings by Carstens, inspired by ancient cameos and gems of Lippert's Dactyliotheca and the Stosch collection.